The role of α2,3-linked sialylation on clear cell type epithelial ovarian cancer - Pi-Lin Sung; Kuo-Chang Wen; Huann-Cheng Horng; Chia-Ming Chang; Yi-Jen Chen; Wen-Ling Lee; Peng-Hui Wang (Elsevier, 2018)
Objective: Our previous study has shown that high expression of α2,3-sialytransferase type I was associated with advanced stage serous type epithelial ovarian cancer (EOC). The aim of the current study further attempts to evaluate the altered α 2,3-sialylation on the behavior of clear cell type EOC (C-EOC). Materials and methods: Immunohistochemistry staining, bioinformatics analysis and tissue array were used to disclose the clinical significance of over α2,3-sialylation in C-EOC. An α2,3 sialylation inhibitor, soyasaponin I (SsaI) was used to investigate the behavior change of the C-EOC cell line. Results: We reconfirmed that α2,3-sialylation, instead of α2,6- sialylation, was associated with late-stage C-EOC. Soyasaponin I could inhibit α2,3-sialylation of C-EOC cell lines and increase E-cadherin expression with subsequently suppressing migration of C-EOC cells. Conclusions: The current study demonstrated the important role of α2,3-linked sialylation in C-EOC and targeting of α2,3-linked sialylation might offer as a potential therapeutic strategy in the future. Keywords: α2,3-sialylation, Clear cell type, E-cadherin, Epithelial ovarian cancer, Soyasaponin I